Characterization of mannose-binding lectin (MBL) variants by allele-specific sequencing of MBL2 and determination of serum MBL protein levels - Adamek, Martina Maria; Heyder, J.; Heinold, Andreas; Fiedler, Gerd; Opelz, Gerhard; Tran, Thuong Hien (Tissue antigens, 2013)
Mannose-binding lectin (MBL) is a major component of the lectin pathway of complement activation. High and low MBL levels have been associated with susceptibility and severity of a variety of infectious and autoimmune diseases. Several single-nucleotide polymorphisms (SNPs) in the promoter region and exon 1 of the MBL2 gene are responsible for variations in serum MBL levels. We developed a sequence-based typing method for allele-specific MBL2 genotyping and measured serum MBL protein levels in 24 German blood donors. We identified the common MBL2 haplotypes including five promoter polymorphisms in linkage with the Q allele and correlated serum MBL levels with the respective genotypes. The genotyping method presented here could provide a basis for confirmatory studies in larger cohorts.
Gesehen am 05.05.2021